2002
DOI: 10.1519/1533-4287(2002)016<0250:acolad>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Linear and Daily Undulating Periodized Programs with Equated Volume and Intensity for Strength

Abstract: The purpose of this study was to compare linear periodization (LP) and daily undulating periodization (DUP) for strength gains. Twenty men (age = 21 +/- 2.3 years) were randomly assigned to LP (n = 10) or DUP (n = 10) groups. One repetition maximum (1RM) was recorded for bench press and leg press as a pre-, mid-, and posttest. Training involved 3 sets (bench press and leg press), 3 days per week. The LP group performed sets of 8 RM during weeks 1-4, 6 RM during weeks 4-8, and 4 RM during weeks 9-12. The DUP gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
156
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 106 publications
(166 citation statements)
references
References 9 publications
3
156
2
5
Order By: Relevance
“…DUP demonstrated a statistically significant superiority in enhancing strength [9,14,16,20,21,[42][43][44] and vertical jump performance [14,42,44] vs. single-set programs [14,42,44], non-periodized multiple-set programs [9,16,43], and SPP models [16,20,21]. Other studies found equal gains between DUP and SPP in strength [8,10,13,15,18] and speed-strength performance [10,13] with subjects with a low to moderate performance level.…”
Section: Periodization Models Of Mesocycle Lengthmentioning
confidence: 98%
See 4 more Smart Citations
“…DUP demonstrated a statistically significant superiority in enhancing strength [9,14,16,20,21,[42][43][44] and vertical jump performance [14,42,44] vs. single-set programs [14,42,44], non-periodized multiple-set programs [9,16,43], and SPP models [16,20,21]. Other studies found equal gains between DUP and SPP in strength [8,10,13,15,18] and speed-strength performance [10,13] with subjects with a low to moderate performance level.…”
Section: Periodization Models Of Mesocycle Lengthmentioning
confidence: 98%
“…In DUP studies, common repetition zones for strength-power sessions ranged between 2-4 and 4-6 repetitions, for hypertrophy sessions between 8 and 12 [10,13,14,16,21,22,[42][43][44], and for strength endurance sessions between 12 and 15 [13,14,16,21,[42][43][44] and 20-25 [10]. Other studies alternated hypertrophy sessions with strength-power and speed-strength days [13] (30 % of onerepetition maximum = 1 RM) or with one or two strengthpower sessions [15,20,47], whereas Harris et al [9] alternated only between strength-power and speed-strength days (30-60 % 1 RM) and different exercises.…”
Section: Periodization Models Of Mesocycle Lengthmentioning
confidence: 99%
See 3 more Smart Citations